The physical geography of Western Europe - Koster, Eduard A. (Oxford regional environments., 2005)
The Physical Geography of Western Europe is designed to be a state-of -the-art evaluation of the physical environment of Western Europe, being both retrospective and prospective in its perception of environmental change. The unique natural and regional environments of Western Europe are discussed, as well as the physical geographic framework of the region. Particular emphasis is placed on the impact and responses of human society on the physical environment of the region which is. characterized by a very high population density. As an enhanced reference work it will be of enduring value. - ;A.